2017
DOI: 10.1590/1678-4162-9238
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição do ácido linoleico conjugado no cultivo in vitro de embriões F1 Holandês x Zebu na sobrevivência pós-vitrificação

Abstract: Efeito da adição do ácido linoleico conjugado no cultivo in vitro de embriões F1 Holandês x Zebu na sobrevivência pós-vitrificação

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…All photos were converted to black and white (32 bt), and the oocytes included in antral follicles were delimited and analyzed using the area of integrated density compared. This evaluation was performed in the Image J ® software according to Leite et al (2017) .…”
Section: Methodsmentioning
confidence: 99%
“…All photos were converted to black and white (32 bt), and the oocytes included in antral follicles were delimited and analyzed using the area of integrated density compared. This evaluation was performed in the Image J ® software according to Leite et al (2017) .…”
Section: Methodsmentioning
confidence: 99%
“…Five in vitro embryo culture routines were performed, considering each routine as a repeat and for each repeat it was used five to six replicates. All procedures for in vitro embryo production were based on Leite et al 21 . Briefly, small ovarian follicles containing immature oocytes were punctured to obtain cumulus-oocyte complexes (COCs).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid accumulation is associated with loss of embryonic viability and an increase in lesions caused by cryopreservation, especially in the early stages of embryonic development (80) . Leite et al (41) . showed that the supplementation of culture media with trans-10 conjugated linoleic acid isomer, cis-12 reduced the deposition of intracytoplasmic lipids in embryonic cells.…”
Section: Effect Of Cla Supplementation On Embryo Cryopreservationmentioning
confidence: 98%
“…One of the main effects of CLA supplementation on embryo cryopreservation is the reduction in the expression of enzymes, caused by chemical agents responsible for triglyceride catalysis, reducing lipid exposure in embryonic cells (6) . Additionally, Leite et al (41) proposed that the addition of CLA in the culture medium can affect enzymatic digestion of the zona pellucida, altering the hatching rate of embryos.…”
Section: Cla Regulates Cell Membrane Functionalitymentioning
confidence: 99%